JHEA, Volume 13, n°1 & 2, 2015 - Full Issue - sysetem, journal (Journal of Higher Education in Africa, 2021)
Contents Editorial ........................................... v Surpassing the Spectre of Impossibility: Ideational Impoverishment and the Quest for Sustainable Rural Learning Ecologies in Africa Ato Kwamena Onoma ..................................... 1 Using Indigenous Games to Teach Problem-solving in Mathematics in Rural Learning Ecologies Tshele John Moloi .............................. 21 Sustainable Rural Learning Ecologies: A Pathway to Acknowledging African Knowledge Systems in the Arena of Mainstream of Knowledge Production? Milton M. Nkoane ..................................... 33 Exploring Strategies to Strengthen Continuing Professional Development of Teachers in Rural South Africa Cias T. Tsotetsi & Sechaba Mahlomaholo ....................... 45 An Investigation into the Effectiveness of the University Curriculum in Preparing Pre-service Technology Teachers Sylvia M. Ramaligela, Ugorji I. Ogbonnaya & Andile Mji ............... 75 ‘From Cradle to Grave’: Transforming South Africa’s Learning Ecologies Lebusa Monyooe ........................................... 89 Improving the Quality of Education Among Rural Learners Through the Use of Open and Flexible Approaches in Lesotho’s Secondary Schools Thabiso Nyabanyaba ......................... 111 Transformative Autonomy: Mixed Notes from Teachers to Higher Education Willy Nel ..................................... 133 School–University Partnerships for Professional Development of Teachers: A Case of Lesson Study Intervention in Mathematics Maleho D. Letloenyane & Loyiso C. Jita ........................ 147 Strategies and Outcomes of Involving University Students in Community Engagement: An Adaptive Leadership Perspective Dipane Hlalele, Desiree Manicom, Julia Preece & Cias T. Tsotetsi ..... 169 Creating Sustainable Learning Environments for Professional Curriculum Leadership through Information and Communication Technologies Molaodi Tshelane & Sechaba Mahlomaholo ......................... 193 Accounting Teacher Preparation: A Critical Accounting Perspective Makeresemese R. Qhosola ........................ 213 Creating Effective Postgraduate Learning Environments: An Analysis of an Intervention from Realist Social Theory Sechaba Mahlomaholo ........................... 229